Burden and factors associated with perceived stress amidst COVID-19: a population web-based study in Pakistan - Maryam Pyar Ali Lakhdir; Romaina Iqbal; Nargis Asad; Apsara Ali Nathwani; Syed Iqbal Azam; Ghazal Peerwani (BMJ Open)
Objective This study aims to determine the burden and factors associated with perceived stress in the Pakistani population amidst the COVID-19 pandemic.Setting A web-based cross-sectional survey was conducted from April to August 2020.Population This survey was broadcasted on the web using a Google form link and 1654 Pakistani residents had completed this survey. Individuals belonging to any province, city, village, or district of Pakistan irrespective of any age, having internet access and a link of Google form, with English/Urdu competency, consent to participate, and currently residing in Pakistan were eligible to participate.Outcome measure Perceived stress was measured using a validated tool of perceived stress scale-10. Multiple ordinal regression was used, and an adjusted OR along with a 95% CI are reported.Results The mean score of perceived stress was 19.32 (SD ±6.67). Most of the participants screened positive for moderate (69%) and high levels (14%) of stress, respectively. The odds of high-perceived stress among severely anxious participants were 44.67 (95% CI: 21.33 to 93.53) times than participants with no/minimal generalised anxiety during the complete lockdown. However, the odds of high levels of perceived stress among moderately anxious respondents were 15.79 (95% CI: 10.19 to 24.28) times compared with participants with no/minimal anxiety during the smart lockdown.Conclusion This study evidence that the pandemic was highly distressing for the Pakistani population causing the maximum level of perceived stress in more than half of the population. Adequate and timely interventions are needed before high-stress levels culminate into psychological disorders.